2012
DOI: 10.1088/0957-0233/23/8/085701
|View full text |Cite
|
Sign up to set email alerts
|

An interfacial stress sensor for biomechanical applications

Abstract: This paper presents a capacitive sensor that measures interfacial forces in prostheses and is promising for other biomedical applications. These sensors can be integrated into prosthetic devices to measure both normal and shear stress simultaneously, allowing for the study of prosthetic limb fit, and ultimately for the ability to better adapt prosthetics to individual users. A sensing cell with a 1.0 cm2 spatial resolution and a measurement range of 0–220 kPa of shear and 0–2 MPa of pressure was constructed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…A planeshear strain gage rosette was first demonstrated in [20]. Current developments of shear stress sensors are based on MEMS technology [21], including piezo-resistive [22] or capacitive [23,24] shear stress sensors. More recently, Missine et al [25] demonstrated an optoelectronic shear sensor based on measuring the optical power with a photodiode received from a vertical cavity surface-emitting laser facing the photodiode and separated with a deformable transduction layer.…”
Section: Introductionmentioning
confidence: 99%
“…A planeshear strain gage rosette was first demonstrated in [20]. Current developments of shear stress sensors are based on MEMS technology [21], including piezo-resistive [22] or capacitive [23,24] shear stress sensors. More recently, Missine et al [25] demonstrated an optoelectronic shear sensor based on measuring the optical power with a photodiode received from a vertical cavity surface-emitting laser facing the photodiode and separated with a deformable transduction layer.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to produce sensors capable of measuring the pressure within prosthetic sockets have tended to involve piezoresistive [21][22][23], piezoelectric [24][25][26], capacitive [27][28][29][30], optical sensors [31][32][33][34][35][36][37] and microelectromechanical (MEMs) sensors [38][39][40][41].…”
mentioning
confidence: 99%
“…81 139 They are the key representatives of prosthesis to body load transfer. 156 The magnitude of TT interfacial ranged from 0.4 to 76.2-79.6 kPa at the anterior medial region during stance. 134 140 Excessive shear over the stump leads to local separation of dermis from epidermis followed by fluid deposition and blister formation (Sanders et al, 1993b).…”
Section: Interfacial Shear Stressmentioning
confidence: 97%
“…rightdiagnosis.com/a/amputation/prevalence.htm, accessed on 26-09-2012). Prevalence of LL amputation in USA is 623000 156 whereas its annual incidence in UK is 5500. 22 42 According to National Limb Loss Information Centre USA, four major causes have been identified for amputation which are Vascular disease, Trauma, Cancer and Congenital anomalies 46 as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%